If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8r + -3) + -1(7r + 1) = 6 Reorder the terms: (-3 + 8r) + -1(7r + 1) = 6 Remove parenthesis around (-3 + 8r) -3 + 8r + -1(7r + 1) = 6 Reorder the terms: -3 + 8r + -1(1 + 7r) = 6 -3 + 8r + (1 * -1 + 7r * -1) = 6 -3 + 8r + (-1 + -7r) = 6 Reorder the terms: -3 + -1 + 8r + -7r = 6 Combine like terms: -3 + -1 = -4 -4 + 8r + -7r = 6 Combine like terms: 8r + -7r = 1r -4 + 1r = 6 Solving -4 + 1r = 6 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 1r = 6 + 4 Combine like terms: -4 + 4 = 0 0 + 1r = 6 + 4 1r = 6 + 4 Combine like terms: 6 + 4 = 10 1r = 10 Divide each side by '1'. r = 10 Simplifying r = 10
| 6b+8=-7+3b | | 3(x-1)-(x-3)+5(x-2)=18 | | 12x^2+18x-8=32x^3-5+10x | | 24g=4 | | -8n-n=-6-8n | | p+20=60 | | x+4/3=2/5 | | 5(2n-3)-6n=3(3n+5) | | x^4+36=-13x^2 | | c+11=22 | | X-3(x-4)=3x-19(4) | | f+21=36 | | 0=5+2(3+4x) | | 4x+6y=152 | | X*2+2=10 | | 4x+6x=152 | | 2x^2-23x-162=0 | | (x*.05)+x=19 | | x^5+3x^4-8x^3-24x^2-9x-27=0 | | 4(k-6)-3(3k-11)=12 | | x-8= | | 6x-15=9x-6 | | 4x^6-8x^5-7x^4+7= | | X+4=x-6 | | 0.16(0.82+d)=-3 | | (72x)922=4317 | | 9r+4r+6-2=9r+4+3r | | 9x+7x= | | 6+5x=8+2x+2x | | 5t-16=4 | | 7x-29-21x=5-2(6+x) | | 4(r+1)-3(3r+1)=11 |